CONSUMER PROFILE OF A FAST FOOD RESTAURANT IN MALL PLAZA MAULE, CHILE - Portes Júnior, Moacyr; Montecino, Patricio Wladimir Gurtiérrez; Figueroa, Marcela de la Paz Inostroza; López, Sebastián Eduardo Retamal; Salgado, Natalia de los Ángeles Toloza; Mora, Lisbetty del Pilar Morales (Seven Editora, 2026)
Introduction: Four out of ten Chileans consume junk food at least once a week. Objective: To describe the consumer profile of a fast-food restaurant in the Mall Plaza Maule, Maule, Chile. Methodology: A quantitative, descriptive, non-experimental study with a grounded theory design; sample: 990 subjects over 18 years of age, collected over a one-week period. Instrument: A survey created by the researchers and validated by experts; eight questions: weight/height, age, gender, occupation, educational level, frequency of visits to the fast-food restaurant, what they usually eat, three meals they most often eat, who they go with, the reason for eating, whether they engage in physical activity and how often, and what types of exercise they do. Results: Consumers are predominantly male (82%), young adults (18-40 years old), students or workers with secondary to university education, and an average BMI in the overweight range (20-25%). Consumption frequency is weekly (mainly 1-2 times), with a preference for traditional fast food such as french fries (537), hot dogs (457), pizza (282), and hamburgers (259), over healthy options (258). Consumers visit in the company of friends (282), partners (228), or family (184), motivated by price (372), taste (291), and speed (586). Although 75% engage in physical activity (1-2 times/week, 30 min-2 hours), moderate exercise such as weightlifting, cardio, jogging, or walking predominates, which is insufficient to counteract high caloric intake. Conclusion: Given the Chilean context of overnutrition and obesity, the profile reveals urban lifestyles with a nutritional-activity imbalance, suggesting interventions for healthy menus and the promotion of exercise.